PENGAMBILAN KEPUTUSAN MEMILIH TEMPAT BELANJA DI KEC.TAMPAN KELURAHAN SIMPANG BARU STUDI KASUS : PADA PENGUNJUNG INDOMARET KOTA PEKANBARU - Helmida Yanti; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Human beings are essentially needs, to continue the sustainability of human life must meet the necessities of life, and the more the person's needs will be growing and increasing, to meet the needs of a person's life will be shopping as needed and he wanted to meet the person's needs buyers will choose or decide which place he thinks fit to meet these needs. Shopping decision is an act or process of selecting the buyer, where the person feels fulfilled their needs by shopping someplace better he saw that led to the decision to buy the place. Therefore, a buyer will membanndingan between a shopping place to place resulting in the conclusion that he thought he had to go shopping. Therefore, a buyer will membanndingan between a shopping place to place resulting in the conclusion that he thought he had to go shopping. With the development of sophisticated era and this instant various companies take advantage of the behavior of the daily human consumption which is growing as well as a mini-branded Indomaret, a phenomenon that is increasingly crowded modern stores in Indonesia a few years this one is Indomaret. Minimarket Indomaret is a new bid form provided by a company in the world trade with the concept of shopping and necessities on the roof, and serve grocery shopping in the form of scale. Until the present time we can find in every room of the mini-road presence, in addition to the daily needs of the people selling products Indomaret also hold services and employed several discounts and promotions to attract the public to visit thereto. So as to meet the needs of a consumer does not need to move to another store enough in one way, ie in Indomaret as for the type of services apart from the given daily products offered to consumers is as services Indomaret Card, ATM Indomaret, Western Union, Indomaret Delivery (I- delivery), I-Voucher, I-Kiosk, I-Car, Water Subscription Payments, Microinsurance, Railway tickets, tickets Performances, CD albums, Gallon Water Sales Services, and Mobile pulse handpone. Which of these services there are not operated on Indomaret-specific Indomaret. The method used is a quantitative method of non-inferential, while data collection is done with the interview and sent questionnaires to consumers who become visitors Indomaret to see his decision to pick a spot of shopping in Indomaret.Keywords: Decision Making, Consumer and Shopping Sites